ANALISA HUKUM ATAS TANAH HAK MILIK YANG TERLANTAR BERDASARKAN PERATURAN PEMERINTAH NO. 20 TAHUN 2021 TENTANG PENERBITAN KAWASAN DAN TANAH TERLANTAR - Elbert Elbert; Gustianus Fernando (Fakultas Hukum Universitas Tarumanagara, 2021)
Certificate of property rights is a letter of proof of ownership of property rights that acts as a strong means of evidence. However, property rights can be abolished if the land is abandoned or not utilized properly. As stipulated in Government Regulation No. 20 of 2021 concerning the Issuance of Abandoned Areas andLand, that land with property rights status becomes an object of abandoned land. The formulation of the issues raised is, the legal certainty of property rights that are designated as abandoned land and the Process of Settlement of Abandoned Land based on PP No. 20 of 2001. In this study the authors used this type of normative legal research, which is this study will find and also formulate legal arguments related to abandoned property rights land. The conclusions in this study show that property rights land is the highest pedestal of rights and strengthened by issuing certificates of property rights, but the power of the certificate cannot prevent the removal of property rights status into abandoned land, if the landowner does not utilize the land as the social function that has been established by Uupa No. 5 of 1960.